Economics crisis lexicon: for a didactic and lexical approach in French foreign language - AULITTO, Sabrina; Bidai, Yasmine (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study presents a brief description of the French linguistic lexicon of the economic and financial crisis. It offers two levels of analysis: the first character in teaching French as a foreign language (FFL) and the second proposes a lexical analysis.